model of creative industry management in border areas to improve bilateral cooperation In Indonesia and Malaysia - Elyta Elyta (Taylor & Francis Group, 2021)
Every country has the right to cooperate in supporting its interests including cross-border countries. The creative industry is a sector that impacts the people’s economy in Indonesia, both as a solution to unemployment, accommodating domestic workers, and as a source of foreign exchange. This paper aims to design a creative industry management model in border areas in enhancing bilateral cooperation between Indonesia-Malaysia. This research study was conducted in the border between Indonesia-Malaysia. The study results found that the government had carried out creative industries in border areas by utilizing the potential of natural resources, political support, and infrastructure, such as the Sajingan border crossing. It’s also found the need to accelerate the revision of trade cooperation agreements. The cooperation between Indonesia and Malaysia in developing the creative industry that has been taking place includes the Indonesia-Malaysia Social Economy cooperation and the Border Trade Agreement.